A Synergistic Approach for Enhancing Image Encryption by Implementing Double Random Permutation and Memristive Chaos (International Journal of Engineering and Advanced Technology (IJEAT), 2025)
The growing academic interest in the secure transmission of optical digital images has led to a surge in awareness of information security within photonics circumstances. This work presents a hybrid encryption strategy based on the memristor hyperchaotic system and a double random transform for pictures in the frequency and spatial domains. This study presents a robust and secure picture encryption technique that combines compressed sensing, double random phase encoding (DRPE), and Lorenz map. We also make doublerandom-phase masks using Lorenz maps, which enhance the unpredictability and key sensitivity, thereby improving the security of the encryption method. Experimental studies utilize a range of performance metrics, such as the PSNR, NPCR, MSE, and SSIM, to show the value of the suggested approach.